URICAS SYMPOSIUM 2017 STRENGTHENS BILATERAL COOPERATION - MPRC, Pusat Media & Perhubungan Awam (2017)
USM, PENANG, 27 February 2017 – The collaboration established between Universiti Sains Malaysia (USM) with RIKEN Institute, a leading research institute from Japan, was aimed at promoting scientific progress in the research on ageing science, resulting in both parties developing a range of research on the ageing process through the USMRIKEN Centre of Ageing Science (URICAS).